Farnesol Induces Apoptosis-Like Phenotype in the Phytopathogenic Fungus Botrytis Cinerea - Cotoras-Tadic, M; Mendoza-Espinola, L; Mendoza-Espinola, L; Castro-Valenzuela, P; Castro-Valenzuela, P (2013)
This study demonstrates that the isoprenoid farnesol produces a toxic effect on the phytopathogenic fungus Botrytis cinerea in solid and liquid media. In solid media farnesol retarded 72h the beginning of mycelial growth. Also, it was demonstrated that the toxic effect is due to farnesol triggers apoptosis in B. cinerea because ROS accumulation, DNA fragmentation and phosphatidylserine externalization were detected in farnesol-treated mycelium. Therefore, compounds that increase the intracellular farnesol or induce apoptosis could have a potential application as fungicide against B. cinerea. © 2013 by The Mycological Society of America, Lawrence, KS 66044-8897.